Nanotechnology-based drug delivery of ropinirole for Parkinson's disease - Emilia Barcia; Liudmila Boeva; Luis García-García; Karla Slowing; Ana Fernández-Carballido; Yaquelyn Casanova; Sofía Negro (Taylor & Francis Group, 2017)
A new drug delivery system is developed for ropinirole (RP) for the treatment of Parkinson's disease (PD) consisting of biodegradable poly (D,L-lactide-co-glycolide) (PLGA) nanoparticles (NPs). The formulation selected was prepared with 8 mg RP and 50 mg PLGA 502. This formulation exhibited mean encapsulation efficiency of 74.8 ± 8.2%, mean particle size lower than 155 nm, the zeta potential of −14.25 ± 0.43 mV and zero-order in vitro release of RP (14.13 ± 0.17 μg/h/10 mg NPs) for 5 d. Daily doses of the neurotoxin rotenone (2 mg/kg) given i.p. to male Wistar rats induced neuronal and behavioral changes similar to those of PD. Once neurodegeneration was established (15 d) animals received RP in saline (1 mg/kg/d for 35 d) or encapsulated within PLGA NPs (amount of NPs equivalent to 1 mg/kg/d RP every 3 d for 35 d). Brain histology and immunochemistry (Nissl-staining, glial fibrillary acidic protein and tyrosine hydroxylase immunohistochemistry) and behavioral testing (catalepsy, akinesia, rotarod and swim test) showed that RP-loaded PLGA NPs were able to revert PD-like symptoms of neurodegeneration in the animal model assayed.